PENGARUH LITERASI KEUANGAN, INKLUSI KEUANGAN, DAN INOVASI TERHADAP KINERJA UMKM : THE EFFECT OF FINANCIAL LITERACY, FINANCIAL INCLUSION, AND INNOVATION ON MSMEs PERFORMANCE - Joko Susilo Joko; Yuneita Anisma; Azhari Sofyan (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2022)
This study aims to examine and analyze the effect of financial literacy, financial inclusion, and innovation on the performance of MSMEs in Pekanbaru City. The population of this study is MSMEs scattered in Pekanbaru City which recorded as many as 14,120 MSMEs. The sample used was 78 respondents who were determined by using the purposive sampling technique. The data analysis method used in this study is multiple linear regression analysis, with a significance level of 0,05. Meanwhile, the analytical tool used in this research is the data processing software Statistical Product and Service Solutions (SPSS). The results of the study indicate that financial literacy and financial inclusion have an effect on the performance of MSMEs as evidenced by tcount > ttable. While other findings indicate that innovation ha a no effect on the performance of MSMEs in Pekanbaru City .